TONSILLITES IN CHILDREN: ISSUES OF PATHOGENESIS AND POTENTIAL OF PHYTOTHERAPY - L. R. Selimzyanova; E. A. Vishneva; E. A. Promyslova (Педиатрическая фармакология, 2014)
Inflammation of palatine tonsils (acute and chronic tonsillitis) is a pressing issue of pediatrics. Several pathogenetic links of chronictonsillitis development have not been identified yet despite high prevalence of the disease. The article presents current data onformation of biofilms at chronic tonsillites and immunological peculiarities of the Pirogoff-Waldeyer’s tonsillar ring’s lymphoid tissue in children. Authors emphasize the fact that prescription of antibacterial therapy at inflammation of palatine tonsils must be clearly justified due to the risk of development of microflora resistance, as well as of disturbed natural balance of mouth cavity microbiota. Differential diagnosis of tonsillitis and rare Marshall syndrome is important for determining appropriate management tactics. The authors demonstrated effectiveness of using a complex phytopreparation for acute and chronic tonsillites in children.